Applying the DPSIR Framework to Evaluate Factors Affecting Wastewater Collection and Treatment Policy Mechanisms in Hanoi City - Tran, Trang Mai (International Journal of Humanities, Education, and Social Sciences, 2025)
The rapid urbanization of Hanoi has exacerbated existing challenges in wastewater management, with less than 30% of urban wastewater currently being treated despite ongoing legislative reforms and the adoption of Public-Private Partnership (PPP) models. This study employs the DPSIR (Driver–Pressure–State–Impact–Response) framework to systematically analyze the underlying factors influencing wastewater collection and treatment policies in Hanoi. Using a qualitative methodology that combines document analysis with expert interviews, the research identifies major drivers such as population growth and industrialization, alongside pressures including outdated infrastructure and rising pollution levels. The analysis highlights critical issues such as legal inconsistencies, insufficient financial frameworks, and institutional fragmentation that impede effective policy implementation and the successful deployment of PPPs. In response, the study proposes actionable recommendations, including legal harmonization, financial model restructuring, institutional capacity-building, and increased community engagement. These findings offer valuable insights for policymakers and stakeholders in Hanoi and other rapidly urbanizing cities in developing countries seeking to establish more sustainable and effective wastewater management systems.